Physiological properties of fluid circulation in the crystalline lens in animals with regard to a phase of accommodation (Ukrainian Journal of Ophthalmology, 2026)
Background. Traditional ideas about the fluid circulation in the lens assume its movement through the lens capsule inside-out and its surface distribution in the lens bulk. It is alleged that "fresh" intraocular fluid directionally diffuses from the posterior chambera into the lens toward its center through both its the anterior capsul epithelium and the posterior lens capsule wall. Then intraocular fluid moves along the lamillar structures of the lens towards the equator, where, likely, the Na+, K+-pump activity is maximal. Removal of "waste" of fluid from the lens bag goes in all directions: either through the anterior and posterior capsule, or through the equatorial part.However, these views do not take into account the physiological characteristics of the transport properties of the anterior capsule epithelium that is capable, due to an existing therein ion exchange system, to provide only the one-way fluid flow: from outside to inside. The possible changes in the level of pressure within the lens in different accommodation phases, which may affect the intensity or direction of water exchange, are also not taken into account.The aim of the research. To identify the main mechanisms of the water-exchange process in the lenses of animals, taking into account a phase of accommodation.Materials and Methods. Lenses of rabbits and cattle were studied. The fluid transport processes in the lenses were examined in vitro by changing their weight when placed in incubatory solutions with or without an inhibitor of Na+, K+ -ATPase. In the first part of the in vitro studies, the lens partially (some lenses with the anterior surface, others with posterior surface) were immersed in solutions representing the lens surrounding medium. In the second part of the in vitro study, the lenses were completely immersed in a solution similar in ionic composition to aqueous humor, with different osmotic pressures. The direction of movement of intraocular fluid was studied in vivo according to dye distribution using biomicroscopy and a stopped diffusion method.Results. The epithelium of the anterior lens capsule of rabbits and cattle supports the water transport from the posterior chamber of the eye into the lens through the work of Na+, K+ -ATPase. This active ion transport system facilitates the directed movement of the "fresh" fluid, rich in metabolites, through the anterior capsular epithelium from the anterior surface of the lens capsule to the posterior one.For the first time we found that at the completely "near" accommodation phase  the maximal pressure inside the lens capsule is 6 mm Hg.This state is a dynamic balance for the lens, i.e. the value of the osmotic pressure of 6 mm Hg balances in the lens the level of the mechanical pressure of the capsule. The lens weight right after removing was close to its original weight with the osmotic pressure of 6 mm Hg.When looking completely "far", the lens bag is stretched with a ciliary zonule and minimally compresses the masses inside the lens (minimal intracranial pressure). This contributes to the intensive inflow into the lens of "fresh" fluid. The anterior capsular epithelium of the lens was found to support the water transport from the posterior chamber of the eye into the lens by the active ion transport system Na+, K+ -ATPase. It is important to note that the fluid circulation inside the lens occurs along the osmotic gradient and is always unidirectional from its anterior epithelium to the posterior wall of the capsule. Diffusive fluid circulation inside the lens does not occur through its nucleus, but along the fibers inside the lens, followed by diffusion of the "waste" fluid outward through the posterior surface of the lens into the vitreous chamber. This mechanism of micro changes in the volume and/or fluid replacement in the lens can be thought of as a mechanism of "fluctuations" of the lens volume.Conclusion. The theory of "lens volume fluctuations" at the "near-far" accommodation phases is presented; the theory is confirmed in animal experiments in vivo and in vitro. Understanding this physiological process makes it possible to selectively choose the type of rational correction for more effective inhibition and prevention of the cataract or presbyopic process.
Keywords: animal lens; fluid circulation; osmosis; diffusion; pressure in the lens; accommodation; prevention; rational correction; cataract